2016
DOI: 10.5296/ije.v8i1.8811
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping Strategies in Parents of Children with Physical, Mental, and Hearing Disabilities in Jordan

Abstract: <p>This research aimed to investigate levels of stress in parents of children with disabilities in<br />Jordan, and coping strategies they used to handle these stresses. An Arabic translation of<br />Parental Stress Scale (Berry, &amp; Jones, 1995) and Coping Strategies Inventory (Tobin, et al.,<br />1989) were used on a sample of 134 parents of children with physical, mental, and hearing<br />disabilities enrolled in diurnal special education centers. The results indicted hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
2
16
1
7
Order By: Relevance
“…Coping strategies help to regain the state of psychological equilibrium the individual used to live before. 24 In the present study the higher coping strategy scores were observed for positive reinterpretation and growth [median 15 (14)(15)(16)], use of instrumental social support [median 15{4-16)], active coping [median 14 (13)(14)(15)(16)], religious coping [median 12{4-16)], use of emotional and social support [median 13.5 (4-16)], suppression of competitive activities [median 15 (12)(13)(14)(15)(16)] and planning [median 15 (12)(13)(14)(15)(16) The present study found that the mothers with high stress in comparison to mothers with lower stress adopted suppression of competitive activities [IQR (14-16)] as their coping strategy. On the other hand, mothers with low level of stress compared to those with high stress adopted mental disengagement [IQR (4-6)], focus on and venting of emotions [IQR (4-12)], restraint [IQR (5-10)], and use of emotional and social support [IQR (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)] as coping strategies to overcome parenting stress.…”
Section: Discussionmentioning
confidence: 99%
“…Coping strategies help to regain the state of psychological equilibrium the individual used to live before. 24 In the present study the higher coping strategy scores were observed for positive reinterpretation and growth [median 15 (14)(15)(16)], use of instrumental social support [median 15{4-16)], active coping [median 14 (13)(14)(15)(16)], religious coping [median 12{4-16)], use of emotional and social support [median 13.5 (4-16)], suppression of competitive activities [median 15 (12)(13)(14)(15)(16)] and planning [median 15 (12)(13)(14)(15)(16) The present study found that the mothers with high stress in comparison to mothers with lower stress adopted suppression of competitive activities [IQR (14-16)] as their coping strategy. On the other hand, mothers with low level of stress compared to those with high stress adopted mental disengagement [IQR (4-6)], focus on and venting of emotions [IQR (4-12)], restraint [IQR (5-10)], and use of emotional and social support [IQR (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)] as coping strategies to overcome parenting stress.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of the parents to create favorable conditions for exchanging opinions as well as their failure to transfer and teach necessary attitudes, values, and coping skills will prevent children from mastering craving control methods (Bawalsah 2016). Goli, Emamipour & Javanmard (2010) stated that life skills training leads to a negative attitude toward drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our data, in the literature, it is reported that the difficulties experienced by mothers are collected under titles such as child's future, child's care, failure to fulfill life-related roles (wife, mother), having no social life, marital conflicts, and social exclusion. [4,5,15,28] It is stated that these difficulties experienced by mothers increase their stress experience. [4] In our study, the mothers who experienced concern about the future of their children had lower social support.…”
Section: Discussionmentioning
confidence: 99%
“…Families that have children with intellectual disability have higher levels of depression, deep sadness, loneliness, anger, anxiety [4] and stress. [5] Previous studies reported that families have difficulties in reorganising their live and experience stress in relation to intellectual disability. [6][7][8] Mothers' stress levels are affected by the age and sex of the child with intellectual disability, diagnosis duration, level of intellectual disability, educational level of the mother, lack of knowledge, failure to fulfil roles within family, socioeconomic level of family, cultural structure, care burden, strain in marital relationships, the decrease in participation in social activities, attitude of society toward the child with intellectual disability, and whether the mother receives social support.…”
Section: Introductionmentioning
confidence: 99%